Starting an online business for dummies - Holden, Greg (Wiley Brand, 2013)
Have a computer, an Internet connection, and a dream? Then, you're already on your way to starting your very own online business. This fun and friendly guide can help you turn your big idea into big bucks whether you're expanding your real-world storefront online or creating your own virtual startup. Starting an Online Business For Dummies, 7th Edition will show you how to identify a market need, choose a web hosting service, implement security and privacy measures, open up shop, and start promoting to the world.